Realizar un análisis socio-jurídico al artículo 108 del Código Civil Ecuatoriano. - Propuesta de reforma legal - Castillo Cabeza, Segundo Nelson (2015)
Marriage is a legal institution of great importance to people because many have held, or will at some point in their lives. Therefore, its legal regulation affects a large percentage of the population. In Ecuador marriage is dissolved or terminated by death, final judgment of nullity, final judgment granting the final possession (presumed dead) and final judgment of divorce Divorce is a valid legal institution in the country, whose main effect is the dissolution of marriage, previously established institution of divorce left free to be re remarry or keep their marital status of divorced and no links one with the other person. Our legislation found two types of divorce such as: divorce on any grounds established by law; and divorce by mutual consent is that according to the doctrine that spouses freely and voluntarily express the desire to terminate the marriage. Our law on divorce by mutual consent mentions that: "By mutual consent spouses may divorce. To this effect, the consent shall be expressed as follows: the spouses manifest, in writing, in person or by special prosecutors, before the civil court of the domicile of either spouse " However despite this type of divorce and just enough will and desire to divorce, that is not reflected in the legislation as Article 108 states that: "After the period of two months, at the request of the spouses or special prosecutors, the civil court shall convene them to a conciliation hearing, which, if not express purpose contrary, they express together and voice their final decision to give the marriage dissolved " Ie will have to wait expressing the law sixty days but not the will of the parties, thus breaching the right to liberty and the principle of speed that the Constitution and international treaties mentioned. For these reasons and after a career conclude and as a legal contribution thought advisable to make a legal analysis to Article 108 of the Civil Code, that after that propose a legal reform